Cone beam computed tomography for the assessment of linear scleroderma of the face - C. Di Giovanni; S. Puggina; A. Meneghel; F. Vittadello; G. Martini; F. Zulian (BMC, 2018)
Abstract Background To date, standardized methods for assessing the disease progression of linear scleroderma of the face (LSF) are lacking. Objectives We investigated whether Cone Beam Computed Tomography (CBCT) may represent a reliable tool for assessing linear scleroderma of the face (LSF). Methods Ten patients with LSF and five age-matched controls underwent CBCT assessment. The transverse sections at three anatomic levels of the maxillofacial bones were analyzed. Measurements of soft tissue and total thickness of both affected and unaffected side of the face were made by a standardized methodology. Six raters evaluated CBCTs twice and blindly one from the other. The intra- and inter-rater reliability was assessed by the Intraclass Correlation Coefficient (ICC). Results CBCT was fast and well tolerated by the patients. The inter-rater concordance for the total thickness was excellent, mean ICC 0.75 for patients, 0.89 for controls. The mean ICC for soft tissue thickness was 0.49 for patients, 0.66 for controls. 58.3% of the measurements for patients and 91.2% of those for controls showed excellent ICC results (≥ 0.75). The intra-rater concordance resulted optimal (ICC 0.77-0.99). Conclusions CBCT is a reliable technique to assess skin and bony changes of LSF.